Breeding Season Irruptions of Rough-legged Hawks (Buteo Lagopus) on Insular Newfoundland - Whitaker, Darroch M.; Montevecchi, William A.; Gosse, John W. (ARCTIC, 1996)
Rough-legged hawks (Buteo lagopus Pontoppidan), a species typically associated with more northerly regions, occurred in unusually high numbers on insular Newfoundland in the summers of 1988 and 1993, and some pairs nested in noncoastal areas on the island in 1993. We suggest that the island is an alternative breeding ground for the species during years of low prey abundance on the Labrador Peninsula. Our observations concur with hypotheses that rough-legged hawks nomadically search for nesting territories and exploit areas near the limits of their breeding range during such years. Forest clear-cuts were used for foraging by pairs nesting in interior Newfoundland during 1993, which suggests that forest harvesting may have opened new alternative habitats for rough-legged hawks. Un nombre inhabituellement élevé de buses pattues (Buteo lagopus Pontoppidan), une espèce typiquement associée aux régions nordiques, a été observé sur l'île de Terre-Neuve durant les étés de 1988 et 1993, et quelques couples y ont niché dans les régions non côtières en 1993. Ces observations suggèrent que l'île est une aire de nidification alternative pour l'espèce pendant les années où les proies se font rares sur la péninsule du Labrador. Nos observations concourent à l'hypothèse voulant que les buses pattues utilisent différents territoires de nidification et exploitent les régions à proximité des limites de leur aire de nidification pendant les années où les proies se font rares. Les couples nichant dans les régions non côtières de Terre-Neuve en 1993 se sont régulièrement alimentés dans les coupes à blanc, ce qui suggère que l'exploitation forestière pourrait avoir offert de nouveaux habitats alternatifs pour les buses pattues.